UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MENENTUKAN VOLUM BANGUN RUANG MELALUI PENGGUNAAN ALAT PERAGA KUBUS SATUAN - Suciati, Suciati (Jurnal Pendidikan Guru, 2018)
This research with class action research (PTK), implementation for three cycles, this research data method using observation and test. The subjects of the study were the students of class VI, the indicator of the success of this study is with the average class has meperoleh minimum of at least 70. From the results of student learning outcomes on the subject determines the volume of building space (beams and cubes) reached an average of 64 in cycle I, 68 in cycle II and 85 in cycle III. Based on these results, the use of unit cube props can improve student learning outcomes on the subject. From the observation can also be seen the increase of activity in learning. Suggestion, which can be submitted to class VI teacher in order to be able to use the unit cube props in series of material of choice of volume of wake up space, and student of class VI is expected to practice by using unit cube props to do practice questions determine the volume of wake up space so easy in facing this matter.